High performance electrochemical capacitors based on MnO2/activated-carbon-paper. Issue 24 (28th June 2015) - Cheng, Zhiyu; Tan, Guiping; Qiu, Yongfu; Guo, Bing; Cheng, Faliang; Fan, Hongbo
<x xml:space="preserve">Abstract</x> The composite MnO2/activated-carbon-paper has been reported for the first time and it shows high specific capacitance and remarkable rate capability as an electrochemical capacitor.